General Feasibility of Physical Models of Tree Branches - Tan, Danielle S.; Maiti, Ritwik; Tan, Yi Wei; Wong, Brendan Zhi Jie; Liew, Yuqiang; Tan, Jia Hao; Lee, Daryl Tsen-Tieng; Burcham, Daniel C. (Frontiers in Forests and Global Change, 2022)
We tested both real and model branches of four local tree species in a wind tunnel, for wind speeds up to 20 m/s. The model branches were same-size replicas of the real branches obtained via photogrammetry and 3D-printed or CNC-machined. Real leaves were attached to the models in approximately similar configuration. After comparing the streamwise force, drag coefficient (based on initial frontal area) and streamwise deflection, we found that the models exhibited similar trends to that of the real branches. Although not identical in value, the measurements for the model branches were similar in magnitude to the real branches. In particular, the drag coefficients appeared to approach very similar plateaus. We believe the differences in streamwise force and deflection to be due to the plastic used for the models, as well as perhaps how the leaves were attached to the models. We thus consider these physical models to be generally feasible for studying tree branches.